Curable composition and cured product thereof

The curable composition of an olefin-aromatic vinyl compound-aromatic polyene copolymer with an additive resin addresses the challenges of low dielectric constants and high mechanical strength, achieving effective insulation and adhesion for high-frequency applications.

JP7654738B2Active Publication Date: 2025-04-01DENKA CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023170371
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-20
Filing Date
2023-09-29
Publication Date
2025-04-01
Estimated Expiration
2040-12-01

AI Technical Summary

Technical Problem

Existing insulating materials for high-frequency applications face challenges with achieving low dielectric constants, low dielectric loss tangents, high mechanical strength, and good adhesion to metal foils, particularly copper foils, while maintaining processability and heat resistance.

Method used

A curable composition containing an olefin-aromatic vinyl compound-aromatic polyene copolymer, combined with an additive resin such as a hydrocarbon-based elastomer or polyphenylene ether, which meets specific molecular weight and monomer content conditions, to produce a thermoplastic resin with improved properties.

Benefits of technology

The resulting cured product exhibits excellent low dielectric properties, high mechanical strength at room and high temperatures, and good adhesion to copper foils, making it suitable for high-frequency electrical insulation applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654738000001
    Figure 0007654738000001
  • Figure 0007654738000002
    Figure 0007654738000002
  • Figure 0007654738000003
    Figure 0007654738000003
Patent Text Reader

Abstract

To provide a composition from which a cured body having high dynamic strength (elastic modulus) under room temperature and high temperature can be obtained.SOLUTION: A curable composition satisfies the following conditions (1) to (4), and contains an olefin-aromatic vinyl compound-aromatic polyene copolymer, and an additive resin, wherein the additive resin is one or more selected from the group consisting of a hydrocarbon-based elastomer, polyphenylene ether, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, and an aromatic polyene-based resin. (1) The number average molecular weight of the copolymer is 5,000 or more and 100,000 or less. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 or more and 20 or less, and the content of an aromatic vinyl compound monomer unit is 0 mass% or more and 70 mass% or less. (3) The aromatic polyene is selected from polyenes which have a plurality of vinyl groups and / or vinylene groups in the molecule and have 5 or more and 20 or less carbon atoms, and the content of the vinyl groups and / or vinylene groups derived from an aromatic polyene unit is 1.5 pieces or more and less than 20 pieces per number average molecular weight. (4) The olefin is selected from olefins having 2 or more and 20 or less carbon atoms, and the total of the monomer units of the olefin, the aromatic vinyl compound and the aromatic polyene is 100 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition. In this specification, the term "sheet" also includes the concept of a film. In addition, even if the term "film" is used in this specification, the term "sheet" also includes the concept of a sheet. [Background technology]

[0002] As communication frequencies move into the gigahertz range and higher, there is an increasing need for insulating materials with low dielectric properties. Polyolefins such as polyethylene and aromatic vinyl compound polymers such as polystyrene have no polar groups in their molecular structures and are therefore known to be materials that exhibit excellent low dielectric constants and low dielectric loss tangents. However, because their heat resistance depends on the crystalline melting point or glass transition temperature, there are issues with their heat resistance as electrical insulators, and furthermore, because they are thermoplastic resins, there are issues with the film-forming process (Patent Document 1).

[0003] Fluorine-based resins such as perfluoroethylene have the characteristics of low dielectric constant, low dielectric loss, and excellent heat resistance, but are difficult to process and form into films, making them poorly suited for devices. There are also issues with the adhesive strength to the copper foil of wiring. On the other hand, substrates and insulating materials using post-curing resins such as epoxy resins, unsaturated polyester resins, polyimide resins, and phenolic resins have been widely used due to their heat resistance and ease of handling, but their dielectric constant and dielectric loss are relatively high, and improvements are needed as insulating materials for high frequencies (Patent Document 2).

[0004] An electrical insulating material made of a graft or block copolymer made of olefin-based and styrene-based polymer segments has been proposed (Patent Document 3). This material focuses on the inherent low dielectric constant and low dielectric loss of olefin-based and styrene-based hydrocarbon polymers. The manufacturing method involves general graft polymerization of commercially available polyethylene and polypropylene in the presence of styrene monomer, divinylbenzene monomer, and a radical polymerization initiator, but this method has the problem that the graft efficiency does not increase and the polymer uniformity is insufficient. Furthermore, the obtained polymer contains gel, and there are problems with poor processability and filling properties. This material is a thermoplastic resin and does not have sufficient heat resistance, so it is necessary to add a heat-resistant resin such as 4-methyl-1-pentene. It is difficult to apply this material to a molding method in which it is applied or filled in a specified location and then cured.

[0005] Patent Document 4 describes an insulating layer made of a crosslinked structure containing a hydrocarbon compound having multiple aromatic vinyl groups as a crosslinking component. The cured product of this crosslinking component specifically described in the examples is rigid, and it is considered difficult to fill a large amount of filler.

[0006] Patent Document 5 shows a cured product obtained from a specific polymerization catalyst and made of an ethylene-olefin (aromatic vinyl compound)-polyene copolymer and a non-polar vinyl compound copolymer with a specific composition and blending. The cured product specifically described in the examples of Patent Document 5 has the characteristics of a low dielectric constant and a low dielectric loss tangent, but is very soft, and therefore it is necessary to improve the mechanical strength such as the elastic modulus at room temperature and high temperature. In thin-film insulating materials, such as interlayer insulating materials for FPC and FCCL and coverlay applications, it is preferable to improve the dimensional stability, such as the thickness during the mounting process or during use after mounting. In addition, the cured product of the composition specifically described in the examples has room for improvement in adhesion to metal foil, especially copper foil. Patent Document 6 shows a cured product obtained from a similar specific polymerization catalyst and made of an ethylene-olefin (aromatic vinyl compound)-polyene copolymer and a non-polar vinyl compound copolymer with a specific composition and blending, but the cured product of the composition specifically described in the examples has room for improvement in adhesion to metal foil, especially copper foil, and low-temperature properties. Patent Document 7 also describes a cured product of a composition containing a similar copolymer, but the cured product of the composition specifically described in the Examples has room for improvement in terms of adhesion to metal foil, particularly copper foil.

[0007] Patent Documents 5, 6, and 7 disclose cured products obtained from specific polymerization catalysts and made of ethylene-olefin (aromatic vinyl compound)-polyene copolymers and non-polar vinyl compounds with specific compositions and blends. These curable compositions contain relatively large amounts of monomer components (aromatic vinyl compounds and aromatic polyenes) and are in the form of varnish. For this reason, they not only have an odor, but also have the problem that B-stage sheets (semi-cured sheets) cannot be easily produced. These curable compositions have the problem that the production facilities are complicated. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Special Publication No. 52-31272 [Patent Document 2] Japanese Patent Application Publication No. 6-192392 [Patent Document 3] Japanese Patent Application Publication No. 11-60645 [Patent Document 4] JP 2004-087639 A [Patent Document 5] JP 2010-280771 A [Patent Document 6] JP 2009-161743 A [Patent Document 7] JP 2010-280860 A Summary of the Invention [Problem to be solved by the invention]

[0009] The above-mentioned conventional techniques have not provided a thermoplastic composition that is easily moldable, nor a cured product that has excellent low dielectric properties and high mechanical strength (elastic modulus, etc.) at room temperature and at elevated temperatures, and there is a demand for such a composition. [Means for solving the problem]

[0010] That is, the present invention can provide the following aspects.

[0011] A curable composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer and an additive resin, the curable composition satisfying the following conditions (1) to (4), wherein the additive resin is at least one selected from the group consisting of a hydrocarbon-based elastomer, a polyphenylene ether, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, and an aromatic polyene-based resin. (1) The number average molecular weight of the copolymer is 5,000 or more and 100,000 or less. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass or more and 70% by mass or less. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass %.

[0012] The cured product is obtained from a composition containing an olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies the following conditions (1) to (4) and an additive resin that is at least one selected from the group consisting of a hydrocarbon elastomer, a polyphenylene ether, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, and an aromatic polyene resin, and has a storage modulus at 300°C of 5 × 10 5 Pa or more, preferably 1×10 6 An electrical insulating material having a dielectric constant of 2.0 or more and a dielectric tangent of 0.003 or less and 0.0005 or more at 23°C and 10 GHz. (1) The number average molecular weight of the copolymer is 5,000 or more and 100,000 or less. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass or more and 70% by mass or less. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass %. Effect of the Invention

[0013] The curable composition of the present invention has properties of a thermoplastic resin. Furthermore, a cured product obtained by curing the curable composition has excellent low dielectric properties and high mechanical strength (such as elastic modulus) at room temperature and at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] A more detailed description is given below. In this specification, the olefin-aromatic vinyl compound-aromatic polyene copolymer may be simply referred to as a copolymer. Unless otherwise specified, the numerical range in this specification includes the upper and lower limit values. In this specification, the term sheet also includes the concept of a film. In this specification, the term film has the same meaning as a sheet. In this specification, the term cured body has the same meaning as a cured product. In this specification, the content may also be referred to as the content.

[0015] <Composition> In this specification, the composition (curable composition) may be referred to as a resin composition or a curable resin composition. The composition of the present invention contains the olefin-aromatic vinyl compound-aromatic polyene copolymer having the above-mentioned certain range of composition and molecular weight. The composition further contains a predetermined amount of one or more "additive resins". The composition may further contain "monomers" and "curing agents" described below.

[0016] <Olefin-aromatic vinyl compound-aromatic polyene copolymer> General methods for producing an olefin-aromatic vinyl compound-aromatic polyene copolymer that can be used in the present invention are described in, for example, JP 2009-161743 A, JP 2010-280771 A, and International Publication WO 00 / 37517. The olefin-aromatic vinyl compound-aromatic polyene copolymer (hereinafter sometimes simply referred to as "copolymer" in this specification) satisfies all of the following conditions (1) to (4). (1) The number average molecular weight of the copolymer is 5,000 or more and 100,000 or less, preferably 20,000 or more and 100,000 or less, and more preferably 30,000 or more and 100,000 or less. (2) The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass or more and 70% by mass or less. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 to less than 20, preferably 1.5 to less than 7, and more preferably 2 to less than 5, per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass %.

[0017] The present olefin-aromatic vinyl compound-aromatic polyene copolymer can be obtained by copolymerizing each of the monomers of an olefin, an aromatic vinyl compound, and an aromatic polyene.

[0018] The olefin monomer is at least one selected from α-olefins having 2 to 20 carbon atoms and cyclic olefins having 5 to 20 carbon atoms, and is a compound consisting of carbon and hydrogen without substantially containing oxygen, nitrogen, or halogen. Examples of α-olefins having 2 to 20 carbon atoms include ethylene, propylene, 1-butene, 1-hexene, 1-octene, 1-decane, 1-dodecane, 4-methyl-1-pentene, and 3,5,5-trimethyl-1-hexene. Examples of cyclic olefins having 5 to 20 carbon atoms include norbornene and cyclopentene. The olefin is preferably a combination of ethylene and an α-olefin or a cyclic olefin other than ethylene, or ethylene alone. When ethylene alone or the mass ratio of the α-olefin other than ethylene contained therein / ethylene is 1 / 7 or less, more preferably 1 / 10 or less, the peel strength of the obtained cured body with copper foil or copper wiring can be increased, which is preferable. More preferably, the content of α-olefin monomer units other than ethylene contained in the copolymer is 6% by mass or less, most preferably 4% by mass or less, or the olefin is ethylene alone. In this case, the peel strength with copper foil or copper wiring can be further increased, which is more preferable. In the preferred combination of ethylene and α-olefin other than ethylene, the glass transition temperature of the ethylene-α-olefin-aromatic vinyl compound-aromatic polyene sequence of the finally obtained cured product can be freely adjusted within the range of about -60°C to -5°C, preferably -50°C to -10°C, depending on the type and content of the α-olefin.

[0019] The aromatic vinyl compound monomer is an aromatic vinyl compound having 8 to 20 carbon atoms, and examples thereof include styrene, paramethylstyrene, paraisobutylstyrene, various vinylnaphthalenes, and various vinylanthracenes.

[0020] The aromatic polyene monomer is a polyene having 5 to 20 carbon atoms and having multiple vinyl groups and / or vinylene groups in its molecule, preferably a polyene having 8 to 20 carbon atoms. The aromatic polyene monomer is preferably a polyene having 8 to 20 carbon atoms and having multiple vinyl groups in its molecule, more preferably a compound having an aromatic vinyl structure such as ortho-, meta-, or para-various divinylbenzenes or mixtures thereof, divinylnaphthalene, divinylanthracene, p-2-propenylstyrene, or p-3-butenylstyrene, which is substantially free of oxygen, nitrogen, or halogen and is composed of carbon and hydrogen. In addition, a bifunctional aromatic vinyl compound described in JP-A-2004-087639, for example, 1,2-bis(vinylphenyl)ethane (abbreviation: BVPE), can also be used. Among these, preferably, ortho-, meta-, or para-various divinylbenzenes or mixtures thereof are used, and most preferably, a mixture of meta- and para-divinylbenzene is used. In this specification, these divinylbenzenes are referred to as "divinylbenzenes." When divinylbenzenes are used as the aromatic polyene, they are preferred because they have high curing efficiency and are easy to cure when a curing treatment is carried out.

[0021] The above-mentioned olefin, aromatic vinyl compound, and aromatic polyene monomers may contain other polar groups, such as olefins containing oxygen atoms, nitrogen atoms, etc., aromatic vinyl compounds containing oxygen atoms or nitrogen atoms, or aromatic polyenes containing oxygen atoms or nitrogen atoms, etc., but the total mass of these monomers containing polar groups is preferably 10 mass% or less of the total mass of the present composition, more preferably 3 mass% or less, and most preferably does not contain any monomers containing polar groups. By making it 10 mass% or less, the low dielectric properties (low dielectric constant / low dielectric loss) of the cured body obtained by curing the present composition can be improved.

[0022] The number average molecular weight of the copolymer is 5000 to 100,000, preferably 20,000 to 100,000, more preferably 30,000 to 100,000. By adjusting the number average molecular weight to be within such a range, the composition is less sticky when an additive resin is added in an uncured state, and the effect of improving thermoplasticity is obtained, and further, the composition can be easily given good physical properties such as high breaking strength and high breaking elongation to the finally obtained cured body. If the number average molecular weight is less than 5000, the mechanical properties of the composition in the uncured stage are low and the adhesiveness is high, so that the composition may be difficult to mold as a thermoplastic resin. If the number average molecular weight is higher than 100,000, the moldability may decrease. The content of aromatic vinyl compound monomer units contained in the copolymer is 0% by mass to 70% by mass, preferably 10% by mass to 60% by mass, more preferably 10% by mass to 55% by mass. If the content of aromatic vinyl compound monomer units is more than 70% by mass, the glass transition temperature of the finally obtained cured body of the composition may be near room temperature, and the toughness and elongation at low temperatures may decrease. When the content of aromatic vinyl compound monomer units is 10% by mass or more, the aromaticity of the copolymer is improved, the compatibility with flame retardants and fillers is improved, and the flame retardant does not bleed out, allowing the filler to be filled in. Also, when the content of aromatic vinyl compound monomer units is 10% by mass or more, a cured product of the composition having high peel strength with copper foil or copper wiring can be obtained.

[0023] In the copolymer, the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 1.5 or more and less than 20, preferably 2 or more and less than 20, more preferably 3 or more and less than 10 per number average molecular weight. The content of vinyl groups and / or vinylene groups may be collectively referred to as "vinyl group content" below. If it is less than 1.5, the crosslinking efficiency is low, and it is difficult to obtain a cured body with sufficient crosslinking density. If the vinyl group content is increased, it becomes easier to improve the mechanical properties of the finally obtained cured body at room temperature and high temperature. The vinyl group content derived from aromatic polyene units per number average molecular weight in the copolymer is calculated by the number average molecular weight (Mn) calculated in terms of standard polystyrene obtained by GPC (gel permeation chromatography) method known to those skilled in the art and the 1It can be obtained by comparing the vinyl group content and vinylene group content derived from aromatic polyene units obtained by H-NMR measurement. For example, 1 By comparing the intensities of the peak areas obtained by H-NMR measurement, if the content of vinyl groups derived from aromatic polyene units in the copolymer is 0.095% by mass, and the number average molecular weight calculated as standard polystyrene by GPC measurement is 68,000, the molecular weight of the vinyl groups derived from aromatic polyene units in the number average molecular weight is the product of these, 64.8, which is divided by the formula weight of the vinyl groups, 27, to obtain 2.4. In other words, the content of vinyl groups derived from aromatic polyene units per number average molecular weight in this copolymer is 2.4. 1 The assignment of peaks obtained by H-NMR measurement is known from the literature. 1 A method for determining the composition of a copolymer from a comparison of peak areas obtained by H-NMR measurement is also known. In this specification, the content of divinylbenzene units in a copolymer is determined based on the peak intensity ( 1 The content of divinylbenzene units is calculated from the vinyl group content derived from the divinylbenzene unit, assuming that one vinyl group is derived from one divinylbenzene unit in the copolymer.

[0024] In the present copolymer, the olefin monomer unit content is preferably 30% by mass or more, and particularly preferably 45% by mass or more. The total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100% by mass. When the olefin monomer unit content is 30% by mass or more, the toughness (elongation) of the finally obtained cured body is improved, and cracks during curing, reduction in impact resistance of the cured body, and cracks during heat cycle testing of the cured body do not occur. In the present copolymer, the olefin monomer unit content is preferably 90% by mass or less.

[0025] In the present copolymer, specific examples of suitable olefin-aromatic polyene copolymers not containing aromatic vinyl compound monomer units include ethylene-divinylbenzene copolymer, ethylene-propylene-divinylbenzene copolymer, ethylene-1-butene-divinylbenzene copolymer, ethylene-1-hexene-divinylbenzene copolymer, and ethylene-1-octene-divinylbenzene copolymer.

[0026] In the present copolymer, examples of the olefin-aromatic vinyl compound-aromatic polyene copolymer containing an aromatic vinyl compound monomer unit include an ethylene-styrene-divinylbenzene copolymer, an ethylene-propylene-styrene-divinylbenzene copolymer, an ethylene-1-hexene-styrene-divinylbenzene copolymer, and an ethylene-1-octene-styrene-divinylbenzene copolymer.

[0027] <Additive resin> The composition of the present invention may contain, relative to 100 parts by mass of the copolymer contained therein, a single or multiple resins selected from a hydrocarbon-based elastomer, polyphenylene ether, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, and an aromatic polyene-based resin (hereinafter simply referred to as "additive resin"), preferably in a total amount of 1 to 500 parts by mass, more preferably in a total amount of 1 to 300 parts by mass. As the additive resin, polyphenylene ether and / or a hydrocarbon-based elastomer may be particularly preferably used. Among the hydrocarbon-based elastomers, a conjugated diene-based polymer is preferred. Among the conjugated diene-based polymers, 1,2-polybutadiene is preferred. By using polyphenylene ether and / or 1,2-polybutadiene, it is possible to reduce the amount of monomer used, and for example, a preferred cured product of the present invention can be obtained without using a monomer.

[0028] <Hydrocarbon elastomer> The amount of the hydrocarbon-based elastomer used in the composition of the present invention is preferably 1 to 500 parts by mass, more preferably 1 to 200 parts by mass, based on 100 parts by mass of the copolymer. The hydrocarbon-based elastomer that can be suitably used in the composition of the present invention is a single or multiple elastomers selected from ethylene-based or propylene-based elastomers, conjugated diene-based polymers, aromatic vinyl compound-conjugated diene-based block copolymers or random copolymers, and hydrogenated products thereof. The number average molecular weight of the hydrocarbon-based elastomer is 1000 or more, more preferably 2000 or more, even more preferably 20,000 or more, and most preferably 30,000 or more. The number average molecular weight of the hydrocarbon-based elastomer is preferably 80,000 or less, more preferably 60,000 or less. Examples of ethylene-based elastomers include ethylene-α-olefin copolymers such as ethylene-octene copolymer and ethylene-1-hexene copolymer, EPR, and EPDM, and examples of propylene-based elastomers include atactic polypropylene, low stereoregular polypropylene, and propylene-α-olefin copolymers such as propylene-1-butene copolymer.

[0029] Examples of the conjugated diene polymer include polybutadiene and 1,2-polybutadiene. Examples of the aromatic vinyl compound-conjugated diene block or random copolymer and their hydrogenated products (hydrogenated products) include SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. Suitable 1,2-polybutadiene is available, for example, as a product of JSR Corporation, and is also available from Nippon Soda Co., Ltd. under the product names of liquid polybutadiene: B-1000, 2000, and 3000. Examples of the suitable copolymer containing a 1,2-polybutadiene structure include "Ricon 100" from TOTAL CRAY VALLEY. When the resin or resins selected from these hydrocarbon elastomers are liquid (approximately 300,000 mPa·S or less) at room temperature (25° C.), in particular, from the viewpoint of the handleability and moldability (handleability as a thermoplastic resin) of the composition of the present invention in an uncured state, the amount used is preferably 1 to 30 parts by mass, and more preferably 1 to 20 parts by mass, per 100 parts by mass of the copolymer.

[0030] <Polyphenylene ether> As the polyphenylene ether, a commercially available known polyphenylene ether can be used. The number average molecular weight of the polyphenylene ether is arbitrary, and considering the moldability of the composition, the number average molecular weight is preferably 10,000 or less, and most preferably 5,000 or less. The number average molecular weight is preferably 500 or more, and most preferably 1,000 or more. In addition, when the composition of the present invention is added for the purpose of curing the composition, it is preferable that the molecular end is modified and / or that one molecule has multiple functional groups. Examples of the functional group include functional groups such as allyl groups, vinyl groups, and epoxy groups, and most preferably, radically polymerizable functional groups, such as vinyl groups, particularly (meth)acrylic groups and aromatic vinyl groups. In other words, in the composition of the present invention, bifunctional polyphenylene ethers in which both ends of the molecular chain are modified with radically polymerizable functional groups are particularly preferred. Examples of such polyphenylene ethers include Noryl (trademark) SA9000 manufactured by SABIC, and particularly preferably, bifunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemical Company, Inc. can be used. The amount of polyphenylene ether used in the composition of the present invention is preferably 1 to 200 parts by mass, and more preferably 10 to 100 parts by mass, based on 100 parts by mass of the copolymer.

[0031] <Olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer> Further, for the curing of the present invention, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer may also be added, and particularly preferably, an olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer that satisfies the following conditions (1A) to (4A) may also be added. The olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer referred to here excludes the above-mentioned olefin-aromatic vinyl compound-aromatic polyene copolymer that satisfies the above-mentioned conditions (1) to (4). (1A) The number average molecular weight of the copolymer oligomer is 500 or more and less than 5,000. (2A) The aromatic vinyl compound monomer is an aromatic vinyl compound having from 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is from 0% by mass to 70% by mass. (3A) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and containing multiple vinyl groups and / or vinylene groups in the molecule, and the vinyl group content derived from the aromatic polyene unit is 1.5 or more per number average molecular weight. (4A) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, the olefin monomer unit content is 30 mass% or more, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass%. The amount of the olefin-aromatic vinyl compound-aromatic polyene copolymer used in the composition of the present invention is preferably in the range of 1 to 49 parts by mass relative to 100 parts by mass of the copolymer. From the viewpoint of the handleability and moldability of the composition of the present invention in an uncured state, the amount is preferably in the range of 1 to 30 parts by mass, and particularly preferably in the range of 1 to 20 parts by mass, relative to 100 parts by mass of the copolymer.

[0032] The definitions and methods of determining the olefin, aromatic vinyl compound, aromatic polyene, number average molecular weight, and vinyl group content are the same as those for the copolymer. The method of determining the number average molecular weight of this copolymer oligomer is as follows. The molecular weight was determined as the number average molecular weight (Mn) converted to standard polystyrene using GPC (gel permeation chromatography). The measurement can be performed under the following conditions.

[0033] (Number average molecular weight of 1000 or more) Column: Two TSK-GEL MultiporeHXL-M φ7.8×300 mm (Tosoh Corporation) columns are connected in series. Column temperature: 40℃ Solvent: THF Flow rate: 1.0ml / min. Detector: RI detector (differential refractive index detector)

[0034] (Number average molecular weight less than 1000) Columns: one TSKgel G3000HXL φ7.8×300 mm, one TSKgel G2000HXL φ7.8×300 mm, and four TSKgel G1000HXL φ7.8×300 mm (manufactured by Tosoh Corporation) connected in series. Column temperature: 40℃ Solvent: THF Flow rate: 0.5ml / min. Detector: RI detector

[0035] <Aromatic polyene resin> Aromatic polyene resins include divinylbenzene reactive hyperbranched copolymers (PDV) manufactured by Nippon Steel Chemical & Material Co., Ltd. Such PDVs are described, for example, in the literature "Synthesis of polyfunctional aromatic vinyl copolymers and development of new IPN-type low dielectric loss materials using them" (Kawabe Masanao et al., Journal of the Japan Institute of Electronics Packaging, p. 125, Vol. 12 No. 2 (2009)). Aromatic polyene resins also include aromatic polyene polymer resins having the above-mentioned aromatic polyene monomer as the main constituent unit.

[0036] <Hardening agent> As a curing agent that can be used in the curable composition of the present invention, a known curing agent that can be used for polymerization or curing of conventional aromatic polyenes and aromatic vinyl compounds can be used. Examples of such curing agents include radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators, and preferably radical polymerization initiators can be used. Preferred are organic peroxides and azo polymerization initiators, and can be freely selected depending on the application and conditions. A catalog listing examples of organic peroxides can be found on the NOF Corporation website, for example: https: / / www.nof.co.jp / business / chemical / product01a.html https: / / www.nof.co.jp / business / chemical / product01b.html https: / / www.nof.co.jp / business / chemical / product01c.html It can be downloaded from. Examples of organic peroxides are also described in the catalogs of Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. Also, a known photopolymerization initiator using light, ultraviolet light, or radiation can be used as the curing agent. Examples of curing agents using a photopolymerization initiator include a photoradical polymerization initiator, a photocationic polymerization initiator, and a photoanionic polymerization initiator. Such photopolymerization initiators can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. Furthermore, curing by radiation or electron beam itself is also possible. It is also possible to perform crosslinking and curing by thermal polymerization of the raw materials contained without containing a curing agent.

[0037] There is no particular limit to the amount of the curing agent used, but generally, 0.01 to 10 parts by mass is preferred per 100 parts by mass of the composition. When using a curing agent such as an organic peroxide or an azo polymerization initiator, the curing process is carried out at an appropriate temperature and time, taking into consideration its half-life. In this case, the conditions are arbitrary according to the curing agent, but generally, a temperature range of about 50°C to 180°C is appropriate.

[0038] <Monomer> The amount of the monomer that may be contained in the composition of the present invention is arbitrary, but is preferably 10 parts by mass or less per 100 parts by mass of the copolymer. The composition may not substantially contain a monomer. If the amount of the monomer is 10 parts by mass or less, the uncured composition does not have a viscous property, and molding processing as a thermoplastic resin becomes easy. In addition, if the content of the easily volatile monomer is below a certain level, odor at the uncured stage does not become a problem. When a solvent is added to the composition to make the product in a varnish form, there is a problem that the monomer is lost with the evaporation of the solvent during use, and the substantial content of the monomer is likely to decrease. In addition, when the product is in the form of an uncured sheet, if the monomer is contained in a certain amount or less, the content of the monomer is unlikely to change during storage. The monomer that can be suitably used in the composition of the present invention preferably has a molecular weight of less than 1000, more preferably less than 500. The monomer that can be suitably used in the composition of the present invention is an aromatic vinyl compound monomer, an aromatic polyene monomer, and / or a polar monomer. The monomer is preferably a monomer that can be polymerized by a radical polymerization initiator, and more preferably the aromatic vinyl compound or aromatic polyene. In addition, BVPE (1,2-bis(vinylphenyl)ethane) described in JP-A-2003-212941 can also be suitably used. From the viewpoint of increasing the mechanical strength (elastic modulus) of the cured body at high temperatures, the aromatic polyene is preferably 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the copolymer. In addition, a relatively small amount of polar monomer can be used for the purpose of imparting adhesion to other materials required as an insulating material or improving crosslink density. Examples of the polar monomer include various maleimides, bismaleimides, maleic anhydride, glycidyl (meth)acrylate, triallyl isocyanurate, tri(meth)acryl isocyanurate, trimethylolpropane tri(meth)acrylate, etc. Maleimides and bismaleimides that can be used in the present invention are described in, for example, International Publication WO2016 / 114287 and JP2008-291227A, and can be purchased from, for example, Daiwa Kasei Kogyo Co., Ltd. or Designer Molecules Inc. Of these maleimide group-containing compounds, bismaleimides are preferred from the viewpoints of solubility in organic solvents, high frequency characteristics, high adhesion to conductors, moldability of prepregs, and the like.

[0039] The bismaleimides are preferably those represented by the following formula (B-1).

[0040] Formula (B-1) [ka]

[0041] In formula (B-1), R represents an alkylene group having 5 or more carbon atoms, and L represents a single bond or a divalent linking group. R and L may each independently have a substituent. The maleimide represented by formula (B-1) is preferably represented by the following formula (B-2).

[0042] Formula (B-2) [ka]

[0043] In formula (B-2), R' each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent, A each independently represents an alkylene group having 5 or more carbon atoms which may have a substituent or a divalent group having an aromatic ring which may have a substituent, and n represents an integer of 1 to 10.

[0044] Examples of the maleimides represented by formula (B-2) include compounds represented by the following formula (B-3), in which n represents an integer of 1 to 10. Examples of the compounds represented by formula (B-3) include BMI-1500 (average n value=1.3) manufactured by Designer Molecules Inc.

[0045] Formula (B-3) [ka]

[0046] The bismaleimides may be used as polyamino bismaleimide compounds. The polyamino bismaleimide compounds are obtained, for example, by a Michael addition reaction between a compound having two maleimide groups at the terminal and an aromatic diamine compound having two primary amino groups in the molecule. When a small amount of addition is to be used to obtain high crosslinking efficiency, it is preferable to use a polar monomer having a multifunctional group of two or more functional groups, and examples of such a polar monomer include bismaleimides, triallyl isocyanurate (TAIC), and trimethylolpropane tri(meth)acrylate. The amount of the polar monomer that may be contained in the composition is in the range of 0.1 to 10 parts by mass, preferably 0.1 to 5 parts by mass, relative to 100 parts by mass of the copolymer. By using 10 parts by mass or less, the dielectric constant and dielectric loss tangent of the obtained cured body are lowered. For example, the dielectric constant is lower than 3.0, and the dielectric loss tangent is lower than 0.005.

[0047] <Solvent> An appropriate solvent may be added to the composition of the present invention as necessary. The solvent is used to adjust the viscosity and fluidity of the composition. As the solvent, a volatile one is preferable, and for example, cyclohexane, toluene, ethylbenzene, acetone, isopropanol, etc. are used. The amount of the solvent used is preferably 10 parts by mass or less per 100 parts by mass of the copolymer of the present invention from the viewpoint of moldability and handling of the composition as a thermoplastic resin before curing, and it is more preferable that the solvent is not substantially used from the viewpoint of removal during and after curing. The amount of the solvent not substantially used is preferably 5 parts by mass or less, more preferably 1 part by mass or less, and most preferably 0 parts by mass. In addition, when used as a varnish, it is preferable to add an appropriate solvent to the composition of the present invention. The solvent is used to adjust the viscosity and fluidity of the composition as a varnish. As the solvent, a solvent with a boiling point of a certain degree or more is preferable because the thickness of the applied film becomes uniform when the boiling point at atmospheric pressure is high, that is, when the volatility is low. The preferred boiling point is about 100°C or more at atmospheric pressure, preferably 130°C or more and 300°C or less. Examples of solvents suitable for such varnishes include toluene, xylene, mesitylene, ethylbenzene, limonene, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether, etc. The amount of the solvent used is preferably in the range of 10 to 2000 parts by mass per 100 parts by mass of the composition of the present invention.

[0048] <Composition> The composition of the present invention can further contain one or more selected from a filler, a flame retardant, and a surface modifier. The composition of the present invention can become a matrix of a cured body, and when cured, contains one or more selected from these fillers, flame retardants, and surface modifiers, so that the cured body can easily exhibit impact resistance and toughness even after curing.

[0049] <Filling agent> Also, known inorganic or organic fillers can be added as necessary. These fillers are added for the purpose of controlling the thermal expansion coefficient, controlling the thermal conductivity, and reducing the cost, and the amount used is arbitrary depending on the purpose. The composition of the present invention can contain a large amount of inorganic fillers, and the amount that can be used can reach up to 2000 parts by mass per 100 parts by mass of copolymer. In particular, when adding inorganic fillers, it is preferable to use known surface modifiers, such as silane coupling agents. In particular, when the objective of the present invention is to obtain a composition excellent in low dielectric constant and low dielectric loss, boron nitride (BN) and / or silica are preferred as inorganic fillers, and silica is preferred. Among silicas, fused silica is preferred. From the viewpoint of low dielectric properties, since there is a risk that the dielectric constant will become particularly high if a large amount is added, it is preferable to use less than 500 parts by mass, more preferably less than 400 parts by mass of fillers per 100 parts by mass of copolymer. Furthermore, in order to improve and enhance low dielectric properties (low dielectric constant, low dielectric loss tangent), hollow fillers or fillers with many voids may be added.

[0050] Also, instead of inorganic fillers, organic fillers such as high molecular weight or ultra-high molecular weight polyethylene can be used. From the viewpoint of heat resistance, it is preferable that the organic fillers themselves are crosslinked, and they are preferably used in the form of fine particles or powder. These organic fillers can suppress increases in the dielectric constant and dielectric loss tangent. The most preferable amount of filler used is 1 part by mass or more and less than 400 parts by mass per 100 parts by mass of the copolymer.

[0051] On the other hand, by mixing and dispersing a high dielectric constant insulating filler having a dielectric constant of preferably 3 to 10,000, more preferably 5 to 10,000 at 1 GHz in the composition of the present invention, it is possible to produce an insulating cured body having a high dielectric constant insulating layer having a dielectric constant of preferably 3.1 to 20 while suppressing an increase in the dielectric loss tangent (dielectric loss). By increasing the dielectric constant of a film made of an insulating cured body, it is possible to miniaturize circuits and increase the capacity of capacitors, which can contribute to miniaturization of high frequency electrical components. A high dielectric constant, low dielectric loss tangent insulating layer is suitable for applications such as capacitors, inductors for resonant circuits, filters, and antennas. Examples of the high dielectric constant insulating filler used in the present invention include inorganic fillers or metal particles that have been subjected to insulation treatment. Specific examples are known high dielectric constant inorganic fillers such as barium titanate and strontium titanate, and other examples are specifically described in, for example, JP-A-2004-087639.

[0052] <Flame retardants> A known flame retardant can be used in the composition of the present invention. From the viewpoint of maintaining a low dielectric constant and a low dielectric loss tangent, preferred flame retardants are known organic phosphorus-based flame retardants such as phosphoric acid esters or condensates thereof, known bromine-based flame retardants, and red phosphorus. In particular, among phosphoric acid esters, compounds having multiple xylenyl groups in the molecule are preferred from the viewpoint of flame retardancy and low dielectric loss tangent.

[0053] In addition to the flame retardant, antimony compounds such as antimony trioxide, antimony tetraoxide, antimony pentoxide, and sodium antimonate, or nitrogen-containing compounds such as melamine, triallyl-1,3,5-triazine-2,3,4-(1H,3H,5H)-trione, and 2,4,6-triaryloxy-1,3,5-triazine may be added as a flame retardant assistant. The total amount of these flame retardants and flame retardant assistants is usually preferably 1 to 100 parts by mass per 100 parts by mass of the composition. In addition, 30 to 200 parts by mass of the polyphenylene ether (PPE) resin with low dielectric constant and excellent flame retardancy may be added per 100 parts by mass of the flame retardant.

[0054] <Surface modifier> The composition of the present invention may contain various surface modifiers for the purpose of improving adhesion to fillers, copper plates, and wiring. The amount of the surface modifier used is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the composition of the present invention other than the surface modifier. Examples of the surface modifier include various silane coupling agents and titanate coupling agents. The various silane coupling agents and titanate coupling agents may be used singly or in combination.

[0055] In the present invention, the flow temperature of the curable resin or composition can be adjusted according to the purpose and molding method by changing the blending ratio of the copolymer, monomer, additive resin, and if necessary, solvent of the composition within the above range, or further by changing the blending ratio of the flame retardant, filler, and surface modifier. Specifically, the composition of the present invention can be in the form of a product such as a "thermoplastic composition," a "semi-cured state (such as a B-stage sheet)," or a "varnish."

[0056] The composition of the present invention can be obtained by mixing, dissolving or melting the copolymer and the curing agent as described above, and, if necessary, one or more selected from the group consisting of monomers, solvents, additive resins, fillers, flame retardants and surface modifiers. Any known method can be used for mixing, dissolving or melting.

[0057] <Thermoplastic composition and molded article> The composition of the present invention uses a copolymer having a molecular weight in a certain range or more, and further contains a predetermined additive resin, and therefore exhibits the properties of a thermoplastic resin. Therefore, under conditions that do not cause crosslinking, the composition can be molded into a shape such as a sheet, tube, strip, pellet, etc. in a substantially uncured state by a known molding method for a thermoplastic resin, and then crosslinked (cured). In this specification, the term sheet also includes the concept of a film. In addition, even if the term film is described in this specification, the term sheet also includes the concept of a sheet.

[0058] In addition, preferred embodiments of the present composition are as follows. When the additive resin, excluding the resin that is liquid at room temperature, contains a certain proportion or more of one or more resins selected from the hydrocarbon-based elastomer, polyphenylene ether, olefin-aromatic vinyl compound-aromatic polyene copolymer oligomer, or aromatic polyene-based resin, the composition can be easily molded as a thermoplastic resin in an uncured state. Specifically, the hydrocarbon-based elastomer (excluding the liquid resin) and / or polyphenylene ether can be added in a range of 30 to 200 parts by mass per 100 parts by mass of the copolymer. When the additive resin is liquid at room temperature, the composition can be added in a range of preferably 1 to 30 parts by mass, particularly preferably 1 to 20 parts by mass, per 100 parts by mass of the copolymer. The amount of the monomer that can be used in the present thermoplastic composition is preferably 10 parts by mass or less per 100 parts by mass of the copolymer. The number average molecular weight of the copolymer used is 5,000 to 100,000, preferably 20,000 to 100,000, more preferably 30,000 to 100,000. The thermoplastic compositions described above can be molded into various shapes such as sheets in advance by utilizing their thermoplasticity at or below the active temperature of the curing agent, and can be combined with semiconductor elements, wiring, or substrates and laminates as necessary, and then heated to harden and bond them.

[0059] The composition of the present invention may be provided as a sheet obtained by molding the composition, which is heated and melted at a temperature below the action temperature or decomposition temperature of the curing agent, by a known method. Molding into a sheet may be performed by extrusion molding using a T-die, a two-roll machine, or extrusion lamination onto a substrate film. In this case, the composition, the mass ratio of copolymer / monomer, or the solvent, additive resin, and flame retardant are selected and adjusted so that the composition melts at the action temperature or decomposition temperature of the curing agent or below and becomes solid at around room temperature. In this case, the sheet is substantially in an uncured state. After that, the sheet is processed through various processing and assembly steps, and finally treated at a temperature and time above the action temperature or decomposition temperature of the curing agent to completely cure. Such a method is a general technique used for ethylene-vinyl acetate resin-based crosslinking sealant sheets for solar cells (photovoltaic power generation devices).

[0060] <Molded body in semi-cured state (B-stage sheet, etc.)> The composition of the present invention can also be made into a molded product, such as a sheet or tube, in a partially crosslinked state, for example, a state in which a part of the curing agent contained therein is reacted and semi-cured (so-called B-stage state). For example, by adopting a plurality of curing agents and / or curing conditions with different curing temperatures, it is possible to semi-cur it and control the melt viscosity and fluidity to make it into a B-stage state. That is, it is also possible to mold the present curable resin or composition into an easy-to-handle B-stage sheet by the first-stage curing (partial curing), laminate it on an electronic device or substrate, and then perform the second-stage curing (complete curing) to make it into a final shape. In this case, the composition of the composition, i.e., the mass ratio of copolymer / monomer, is selected, and a solvent, an additive resin, and a flame retardant are added if necessary, and further the composition containing a curing agent such as peroxide is partially cured, adjusted to a sheet shape (B-stage state), molded and assembled into a device, and then heated under pressure to completely cure. As a method for partially curing the composition, any known method can be used. For example, peroxides having different decomposition temperatures are used in combination, and one method is to obtain a semi-cured sheet by treating for a predetermined period of time at a temperature at which only one of the peroxides is substantially active, and finally, to completely cure the sheet by treating for a sufficient period of time at a temperature at which all of the curing agents are active.

[0061] Furthermore, the molded article may be a sheet. The sheet may be uncured (semi-cured) to the extent that the sheet shape can be maintained, or may be completely cured. The degree of curing of the composition can be quantitatively measured by a known dynamic viscoelasticity measurement method (DMA, Dynamic Mechanical Analysis).

[0062] <Varnish-like composition and molded body thereof> The composition of the present invention can be made into a viscous liquid varnish depending on its composition and blending ratio. For example, a sufficient amount of solvent and / or an appropriate amount of liquid monomer can be used to make the composition into a varnish. In particular, when the composition is used as a varnish, it is preferable to add an appropriate solvent to the composition of the present invention. The solvent is used to adjust the viscosity and fluidity of the composition as a varnish. As a solvent, a solvent with a high boiling point under atmospheric pressure, that is, a low volatility, is preferred because it has the advantage of making the thickness of the applied film uniform. A preferred boiling point is about 100°C or higher, preferably 130°C or higher and 300°C or lower, under atmospheric pressure. Examples of solvents suitable for such varnish include xylene, mesitylene, ethylbenzene, limonene, ethylene glycol methyl ether acetate, ethylene glycol monoethyl ether acetate, and ethylene glycol monobutyl ether. The amount of the solvent used is preferably in the range of 10 to 2000 parts by mass per 100 parts by mass of the composition of the present invention. The varnish-like composition of the present invention can also be made by using a polymerization liquid containing the copolymer of the present invention obtained by polymerization. For example, the polymerization liquid may be concentrated or treated to remove residual monomers, and if necessary, solvents, other resin components, various additives, etc. may be added to adjust the component concentrations and solution viscosity, etc., to produce the polymer.

[0063] The varnish can be applied to or impregnated onto a substrate, and the solvent or the like can be removed by drying or the like to produce an uncured or semi-cured molded article. Generally, this molded article has the form of a sheet, film, or tape.

[0064] <Curing> The composition can be cured by a known method, taking into consideration the curing conditions (temperature, time, pressure) of the curing agent contained therein. When the curing agent used is a peroxide, the curing conditions can be determined by taking into consideration the half-life temperature and the like disclosed for each peroxide.

[0065] <Cured product obtained from the composition> The dielectric constant of the cured body obtained from the composition of the present invention at 10 GHz is 3.0 or less and 2.0 or more, preferably 2.8 or less and 2.0 or more, particularly preferably 2.5 or less and 2.0 or more. The dielectric loss tangent is 0.005 or less and 0.0003 or more, preferably 0.003 or less and 0.0005 or more. These dielectric constants and dielectric loss tangents can be determined by any method known to those skilled in the art, for example, by the resonator method (cavity resonator perturbation method or balanced disk resonator method). The volume resistivity of the obtained cured body is preferably 1×10 15 Ω·cm or more. These values ​​are preferable values ​​for a high-frequency electrical insulating material of, for example, 3 GHz or more. The copolymer used in the composition of the present invention is relatively soft and has a high tensile elongation, so that the cured product obtained from the composition using the copolymer has a characteristic that it is relatively soft, has high impact resistance, and can follow the thermal expansion of the substrate while exhibiting sufficient mechanical properties. That is, the cured product of the present invention has a tensile modulus measured at room temperature (23°C) of less than 3 GPa, 3 MPa or more, and preferably 5 MPa or more. In particular, when a relatively large amount of filler is blended, the tensile modulus may be 3 GPa or more and 20 GPa or less. In addition, the tensile strength at break is preferably less than 50 MPa, 3 MPa or more, more preferably 5 MPa or more, and the tensile elongation at break is preferably 30% or more and less than 300%, and more preferably 50% or more and less than 250%. In particular, when a relatively large amount of filler is blended, the tensile elongation at break may be less than 30%. The cured product of the composition of the present invention can have sufficient heat resistance for practical use. Specifically, from a practical standpoint, the cured product of the composition of the present invention has a storage modulus at 300°C of 5 × 10 5 Pa or more, preferably 1×10 6Pa or more. Those skilled in the art can easily prepare a cured product by determining the composition formulation having the above physical property parameters with reference to the information described in this specification and the publicly known documents. The cured product obtained from the composition of the present invention can exhibit practically sufficient heat resistance and mechanical properties at high temperatures even under conditions in which the aromatic polyene as a monomer or a component of the monomer in the composition is suppressed to a certain ratio or less. As described above, suppressing the aromatic polyene as a monomer or a component of the monomer to a certain ratio or less is also important in order to maintain the moldability as a thermoplastic resin even in an uncured state.

[0066] <General uses of the composition> The composition of the present invention can be used as various insulating materials for wiring, preferably for high-frequency signal wiring, such as coverlays, solder resists, build-up materials, interlayer insulating agents, bonding sheets, interlayer adhesives, and bump sheets for flip-chip bonders.Furthermore, it can be used as an electrical insulating layer or adhesive layer for substrates and boards, such as single-layer or multi-layer printed circuit boards, flexible printed circuit boards, CCL (copper clad laminate), and FCCL (flexible copper clad laminate) substrates.

[0067] <Use of the composition as an uncured or partially cured sheet> The uncured or partially cured sheet of the composition of the present invention can be suitably used as a high-frequency electrical insulating material. For example, it can be suitably used as a build-up film, a bonding sheet, a coverlay sheet, a bump sheet for a flip chip bonder, or an insulating layer or an adhesive layer for a substrate. It can be used as a substitute for conventionally used epoxy resin or silicone resin sheets, and can be cured to form a cured insulating layer or a cured matrix phase with a low dielectric constant and low dielectric loss. The thickness of the sheet is generally 1 to 300 microns. The sheet may contain or be impregnated with woven or nonwoven fabrics such as glass cloth or ceramic fibers, or may be multi-layered with these. In addition, as an antenna cable for a mobile phone or the like, a flexible and bendable wiring that is partially or completely insulated with the sheet can be used instead of a conventional coaxial cable. For example, the sheet of the present invention or the B-stage sheet (coverlay sheet) can be used as an insulating material by covering wiring with a substrate of LCP (liquid crystal polymer), PPE sheet, fluorine-based resin, or polyimide resin, curing the wiring, and adhering it to the substrate.

[0068] A multilayer wiring board in which the cured product obtained by using the composition of the present invention is an insulating layer can be a wiring board with excellent high frequency characteristics with low dielectric loss. In this case, in addition to low dielectric loss, the advantages are heat resistance that can withstand soldering, and a certain degree of softness, elongation, and impact resistance that can withstand stress due to heat cycles or thermal expansion differences. For example, a wiring board can be produced by laminating and pressing a core material such as a cloth made of glass or quartz, a nonwoven fabric, a film material, a ceramic substrate, a glass substrate, a general-purpose resin plate such as epoxy, a general-purpose laminate, etc., and a conductor foil with an insulating layer made of the present cured product. Alternatively, a slurry or solution containing the present composition may be applied to the core material, dried, and cured to form an insulating layer. The thickness of the insulating layer is generally 1 to 300 microns. Such a multilayer wiring board can also be used by multilayering and integrating.

[0069] The cured product obtained by curing the varnish-like composition of the present invention, in particular, can be suitably used as an electrical insulating material as described above, and in particular can be used as a potting material, surface coating agent, coverlay, solder resist, build-up material, underfill material, filling insulating agent, interlayer insulating agent, or interlayer adhesive, or as a cured product for a printed circuit board, a flexible printed circuit board, or an FCCL (flexible copper clad laminate) substrate, or as a build-up film, a bonding sheet, a coverlay sheet, or a cured product for a bump sheet for a flip-chip bonder, and can be used as an electrical insulating material, in particular an electrical insulating material for high frequencies.

[0070] In another aspect, the present invention includes an olefin-aromatic vinyl compound-aromatic polyene copolymer, and the copolymer has a storage modulus of 5×10 at 300° C. 5 The electrical insulating material has a dielectric constant of 2.0 to 2.5 Pa at 23°C and 10 GHz, and a dielectric loss tangent of 0.003 to 0.0005.

[0071] The uncured or semi-cured thermoplastic composition of the present invention can be bonded to a metal foil for wiring, particularly a copper foil, by heat and pressure treatment, without applying an adhesive or performing an adhesive treatment. Here, the copper foil is a concept including copper wiring, and can have any shape. In particular, when a copolymer containing 10% by mass or more of aromatic vinyl compound is used in the olefin-aromatic vinyl compound-aromatic polyene copolymer, and / or the olefin is ethylene alone, or the mass ratio of the olefin monomer component other than ethylene to the ethylene monomer component contained in the olefin is 1 / 7 or less, a peel strength of 1 N / mm or more can be obtained as measured according to Japanese Industrial Standards (JIS) C6481:1996. It is more preferable to obtain a peel strength of 1.3 N / mm or more. More preferably, in the above copolymer, the olefin is ethylene alone, or the olefin monomer component other than ethylene is 1 / 10 or less to the ethylene monomer component contained in the olefin, and most preferably, the content of α-olefin monomer units other than ethylene contained in the copolymer is 4% by mass or less, or the olefin is ethylene alone, the peel strength can be further improved. It is generally known that the dielectric properties of laminates such as copper-clad laminate sheets are deteriorated by the use of adhesives or adhesive treatments, and it is preferable that the composition has a peel strength of 1 N / mm or more when measured according to Japanese Industrial Standards (JIS) C6481:1996 without such treatments. Thus, the uncured or semi-cured thermoplastic composition of the present invention can be bonded to copper foil for wiring by a curing treatment such as a heat and pressure treatment, without the need for adhesive application or adhesive treatment. However, in the present invention, there is no prohibition on carrying out other measures for imparting adhesion to copper foil or other members (adhesive application, adhesive treatment, etc.) including the addition of the above-mentioned "surface modifier".

[0072] In another embodiment of the present invention, there is also provided a curable composition comprising an olefin-aromatic vinyl compound-aromatic polyene copolymer satisfying the following conditions (1) to (4), and more than 0 part by mass and not more than 10 parts by mass of a monomer per 100 parts by mass of the copolymer, wherein the monomer is one or more selected from the group consisting of an aromatic vinyl compound monomer, an aromatic polyene monomer, and a polar monomer. (1) The number average molecular weight of the copolymer is 5,000 or more and 100,000 or less. (2) The aromatic vinyl compound monomer in the copolymer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass or more and 70% by mass or less. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of vinyl groups and / or vinylene groups derived from aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having 2 to 20 carbon atoms, and the total of the olefin monomer units, aromatic vinyl compound monomer units, and aromatic polyene monomer units is 100 mass %.

[0073] More preferably, the monomer may be a polar monomer.

[0074] The curable composition is cured to obtain a cured product having a storage modulus of 5×10 at 300° C. 5 Pa or more, preferably 1×10 6 It is also possible to provide an electrical insulating material having a dielectric constant of 2.0 to 2.5 Pa at 23° C. and 10 GHz, and a dielectric loss tangent of 0.003 to 0.0005.

[0075] The present curable composition can contain one or more selected from the group consisting of the solvent, curing agent, filler, flame retardant, and surface modifier, in the same manner as the curable composition containing the olefin-aromatic vinyl compound-aromatic polyene copolymer and resin (hereinafter simply referred to as the composition with resin). The present curable composition can be molded into various shapes including sheets, such as the composition with the resin, by taking advantage of its thermoplasticity. The present curable composition can be used as a varnish together with a solvent, in the same manner as the composition with the resin. The present invention is a cured product obtained by curing the present curable composition, and can exhibit various physical properties similar to those of the cured product of the composition with the resin. The present curable composition can be formed into a laminate containing a layer containing the curable composition and a copper foil, in the same manner as the composition with the resin, and can also be formed into a cured product obtained by curing the present laminate.

[0076] The composition according to the above-mentioned embodiment of the present invention, or the composition according to other embodiment of the present invention, can be cured together with an LCP (Liquid Crystal Polymer) layer under relatively mild curing conditions to provide high adhesive strength. The LCP layer may specifically be an LCP sheet or film. Therefore, for example, it can be various laminates containing an LCP sheet, a metal foil, preferably a copper foil, and the composition of the present invention. The number of layers of the laminate and the order of lamination are optional. As such an example of the present invention, the composition of the present invention is useful as an adhesive layer between a metal foil (copper foil) and an LCP sheet. The composition of the present invention can exhibit high adhesiveness to both the metal foil and the LCP sheet. Conventionally, the adhesion between an LCP sheet and a copper foil required heating to the melting point of the LCP (approximately 280°C to 330°C, or a temperature close thereto) and pressing. However, by using the composition of the present invention as an adhesive layer, it is possible to bond the LCP and the metal foil at a lower temperature, substantially by pressing at a temperature close to the curing temperature of the composition of the present invention. In this case, the low dielectric constant and low dielectric loss tangent value of the cured product of the composition of the present invention impart usefulness to the laminate, particularly as wiring for high-frequency signal transmission. Another example of the laminate of the present invention is a structure in which a metal wiring, preferably a copper wiring, arranged on an LCP layer is covered with a cured layer of the composition of the present invention from the side opposite the LCP layer, as a so-called coverlay on the LCP substrate wiring.

[0077] Here, LCP (liquid crystal polymer) refers to a thermoplastic polymer that has a liquid crystal state or optically birefringent properties when melted. Examples of LCP include lyotropic liquid crystal polymers that exhibit liquid crystallinity in a solution state and thermotropic liquid crystal polymers that exhibit liquid crystallinity when melted. Liquid crystal polymers are classified into I type, II type, and III type depending on the heat deformation temperature, and any type may be used. Examples of liquid crystal polymers include thermoplastic aromatic liquid crystal polyesters, and thermoplastic aromatic liquid crystal polyester amides in which amide bonds are introduced therein. The LCP may be a polymer in which an isocyanate-derived bond such as an imide bond, a carbonate bond, a carbodiimide bond, or an isocyanurate bond is further introduced into an aromatic polyester or an aromatic polyester amide. The LCP may be a molten liquid crystal forming polyester consisting of 2-hydroxy-6-naphthoic acid and parahydroxybenzoic acid, for example, LCP resin (product number A-5000, melting point 280°C) manufactured by Ueno Pharmaceutical Co., Ltd.

[0078] The melting point of the LCP is preferably 220 to 400°C, more preferably 260 to 380°C, as determined by the DSC method. When the melting point is within the above range, a film or sheet having excellent extrusion moldability and excellent heat resistance can be obtained. Such an LCP can be obtained, for example, from Ueno Pharmaceutical Co., Ltd., Sumitomo Chemical Co., Ltd., and Polyplastics Co., Ltd. Here, the LCP sheet refers to a known LCP sheet, and the thickness thereof is optional. The LCP sheet can be obtained by a known method such as a T-die extrusion method, an inflation method, or an endless belt (double belt press) method. EXAMPLES

[0079] The present invention will be described below with reference to examples, but the present invention should not be construed as being limited to the following examples.

[0080] The copolymers obtained in the Synthesis Examples and Comparative Synthesis Examples were analyzed by the following methods.

[0081] The content of vinyl group units derived from ethylene, hexene, styrene, and divinylbenzene in the copolymer is determined by: 1 The measurements were performed using H-NMR from the peak area intensities assigned to each compound. The sample was dissolved in deuterated 1,1,2,2-tetrachloroethane, and the measurements were performed at 80 to 130°C.

[0082] The molecular weight was determined as a number average molecular weight (Mn) converted to standard polystyrene using GPC (gel permeation chromatography) under the following conditions. (Number average molecular weight of 1000 or more) Column: Two TSK-GEL MultiporeHXL-M φ7.8×300 mm (Tosoh Corporation) columns were connected in series. Column temperature: 40℃ Solvent: THF Flow rate: 1.0ml / min. Detector: RI detector (differential refractive index detector)

[0083] When the copolymer is difficult to dissolve in THF solvent, for example, when the styrene content is lower than 40 mass% in an ethylene-styrene-divinylbenzene copolymer, the molecular weight in terms of standard polystyrene was determined by the following high-temperature GPC method. The measurement was performed under the following conditions. Equipment: Tosoh HLC-8121GPC / HT Column: TSKgelGMHHR-H(20)HT, φ7.8×300mm x 3, Column temperature: 140°C, Detector: RI, Solvent: orthodichlorobenzene, Flow rate: 1.0ml / min Sample concentration: 0.1 wt / vol%, sample injection volume: 100 μL

[0084] <Tensile test> Conforming to JIS K-6251:2017, a film sheet with a thickness of about 1 mm was cut into the shape of a No. 2 dumbbell 1 / 2 test piece, and using a Tensilon UCT-1T type manufactured by Orientec, measurements were taken at 23°C and a tensile speed of 500 mm / min to obtain the tensile elastic modulus, tensile breaking point strength, and tensile breaking point elongation.

[0085] <DSC Measurement> DSC measurement was carried out using a DSC6200 manufactured by Seiko Instruments Inc. under a nitrogen gas flow. That is, using 10 mg of resin, with 10 mg of α-alumina as a reference, using an aluminum pan, under a nitrogen atmosphere, the temperature was raised from room temperature to 240°C at a heating rate of 10°C / min and then cooled to -120°C at 20°C / min. Thereafter, DSC measurement was carried out while raising the temperature to 240°C at a heating rate of 10°C / min to obtain the glass transition temperature. The glass transition temperature referred to here is the supplementary external glass transition start temperature of JIS K7121:2012, which is the temperature at the intersection of a straight line obtained by extending the low-temperature side baseline to the high-temperature side and a tangent line drawn at the point where the curvature of the stepped change portion of the glass transition is maximized.

[0086] <Measurement of Storage Elastic Modulus and Crosslink Density> Using a dynamic viscoelasticity measuring device (RSA-III manufactured by Rheometric Scientific), measurements were taken in the frequency range of 1 Hz and the temperature range of -60°C to +300°C. A measurement sample (3 mm × 40 mm) was cut out from a film with a thickness of about 0.1 mm to 0.3 mm for measurement to obtain the storage elastic modulus. The main measurement parameters related to the measurement are as follows. Measurement frequency 1 Hz Heating rate 3°C / min Sample measurement length 13 mm Test Type = Dynamic Temperature Ramp (DTempRamp) Initial Static Force 5.0 g Auto Tension Sensitivity 1.0 g Max Auto Tension Rate 0.033 mm / s Max Applied Strain 1.5% Min Allowed Force 1.0g Distortion 0.1%

[0087] <Water absorption rate> Measurements were performed in accordance with ASTM D570-98.

[0088] <Dielectric constant and dielectric loss (dielectric tangent)> The dielectric constant and dielectric tangent were measured using the cavity resonator perturbation method (Agilent Technologies 8722ES network analyzer, Kanto Electronics Application Development cavity resonator) at 23°C and 10 GHz using a 1 mm x 1.5 mm x 80 mm sample cut from the sheet.

[0089] <Volume resistivity> The measurement was performed at room temperature using a film approximately 0.5 mm thick in accordance with JIS K6911:2006.

[0090] <Olefin-aromatic vinyl compound-aromatic polyene copolymer> Copolymers P-1 to P-4 were obtained by appropriately changing the monomer amount, ratio, polymerization pressure, and polymerization temperature with reference to the manufacturing methods described in JP 2009-161743 A, JP 2010-280771 A, and International Publication WO00 / 37517. The total of the olefin monomer unit, aromatic vinyl compound monomer unit, and aromatic polyene monomer unit was set to 100% by mass. Table 1 shows the composition, number average molecular weight, and glass transition temperature of the copolymers.

[0091] The raw materials are as follows: The divinylbenzene used was divinylbenzene (meta-para mixture, divinylbenzene purity 81%) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd. The bifunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight 1200) was prepared by diluting a toluene solution product manufactured by Mitsubishi Gas Chemical Co., Ltd. with toluene, adding a large amount of methanol to perform methanol precipitation, air drying, and drying under reduced pressure to obtain a powdered polyphenylene ether oligomer. The SEBS used was Tuftec H-1041 (number average molecular weight 58000) manufactured by Asahi Kasei Chemicals Corporation. The 1,2-polybutadiene used was liquid polybutadiene: product name B-3000 (number average molecular weight 3200) manufactured by Nippon Soda Co., Ltd. The curing agent used was dicumyl peroxide (product name "Percumyl D") manufactured by NOF Corporation, or 2,5-dimethyl-2,5-bis(t-butylperoxy)hexyne-3 (product name "Perhexyne 25B") manufactured by NOF Corporation.

[0092] [Table 1]

[0093] [Table 2]

[0094] Example 1 Using a Brabender Plasticorder (PL2000 manufactured by Brabender), resin P-1 (ethylene-styrene-divinylbenzene copolymer) and the monomer and resin composition shown in Table 2 (the composition in the table indicates parts by mass) that had been kneaded in advance were added, and the mixture was kneaded for 10 minutes at 120°C and a rotation speed of 30 rpm, and then 1 part by mass of a curing agent (dicumyl peroxide, manufactured by NOF Corporation) was added per 100 parts by mass of the resin and monomer composition, and the mixture was kneaded for 5 minutes under these conditions to prepare a composition. The obtained composition was sandwiched between a mold and two Teflon (registered trademark) sheets, closely attached and sealed, and pressed by a hot press method (120°C, time 5 minutes, pressure 5 MPa) to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.). The obtained sheet together with the Teflon (registered trademark) sheet was sandwiched between glass plates under a load to adhere them tightly, and cured by heat treatment for 30 minutes at 120° C., 30 minutes at 150° C., and then 120 minutes at 180° C. After curing, the glass plates, Teflon (registered trademark) sheet, and mold were removed to obtain a film-like cured product of the composition of the present invention.

[0095] Examples 2 to 6, Comparative Example 1 A composition was prepared according to the same procedure as in Example 1, with the composition shown in Table 2 (the composition in the table indicates parts by mass). Press molding and curing treatment were carried out in the same manner as in Example 1. However, in Example 5, the raw materials other than the curing agent were kneaded at 100°C, a rotation speed of 50 rpm for 10 minutes, and then the curing agent (dicumyl peroxide) was added, and kneading was further carried out for 5 minutes under these conditions. However, in Example 4, Perhexine 25B was used as the curing agent. In Examples 3, 4, and Example 7 described later, 1,2-polybutadiene was added before the addition of the curing agent. The properties (room temperature) of the compositions before curing in Examples 1 to 6 and Comparative Example 1 were all soft resin-like or semi-hard resin-like sheets, which were easy to handle as sheets, and even if peeled off from the Teflon (registered trademark) sheet after pressing, the self-adhesiveness of the sheet itself was low, and it could be handled as a single sheet. The examples that satisfied the preferred conditions of the present invention were easy to mold as a thermoplastic resin in an uncured state.

[0096] Examples 7 to 8, Comparative Examples 2 to 4 In a container equipped with a heating / cooling jacket and stirring blade, the raw materials other than the curing agent were charged according to the composition in Table 2, heated to 60°C, and stirred to obtain a varnish-like (viscous liquid) composition. The curing agent was then added and stirred to dissolve. Dicumyl peroxide was used as the curing agent. The obtained varnish-like composition was poured into a Teflon (registered trademark) mold on a Teflon (registered trademark) sheet, and the solvent was thoroughly removed in an air dryer at about 100°C and then under reduced pressure, and then the Teflon (registered trademark) mold was carefully removed to obtain a soft resin-like sheet. The obtained sheet was further sandwiched between the mold and two Teflon (registered trademark) sheets, tightly adhered and sealed, and pressed by a hot press method (120°C, time 5 minutes, pressure 1.5 MPa) to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.). This sheet was easy to handle, and even when peeled off from the Teflon (registered trademark) sheet, the sheet itself had low self-adhesiveness and could be handled as a single sheet. In other words, it was easy to mold and process as a thermoplastic resin in an uncured state. The obtained sheet was sandwiched between glass plates together with the Teflon (registered trademark) sheet, and a load was applied to make them adhere closely, and the sheet was cured by heating at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes. After curing, the glass plates, Teflon (registered trademark) sheet, and mold were removed to obtain a cured sheet of the composition of the present invention.

[0097] The cured sheets obtained in Examples 1 to 8 were capable of measuring the elastic modulus even at 300°C in a viscoelastic spectrum measurement without melting or breaking, and the storage modulus at 300°C (573K) was 5×10 5 The crosslink density calculated from the storage modulus at 300°C (573K) was 3×10 -5 mol / cm 3 The values ​​were higher than those shown in Table 1, indicating that crosslinking had progressed sufficiently. All of the sheets exhibited a tensile modulus of less than 3 GPa and 3 MPa or more. Furthermore, the tensile strength at break was 5 MPa or more and less than 50 MPa, and the tensile elongation at break was 50% or more and less than 250%. The dielectric constant and dielectric tangent also satisfied the ranges of the present invention. The water absorption of the cured sheets obtained in Examples 1 to 8 was less than 0.1% by mass, and the volume resistivity was 1×10 15The dielectric constant measured at 10 GHz was 2.0 or more and 0.003 or less and 0.0005 or more, and the cured sheets obtained in Examples 1 to 8 showed good low dielectric properties. The cured sheet obtained in Comparative Example 1 did not satisfy the conditions of the present invention in terms of storage modulus at 300°C or crosslink density. The sheet obtained in Comparative Example 2 had many cracks and was unsuitable for use as an insulating material, so various physical property measurements were not performed. The sheets obtained in Comparative Examples 3 and 4 did not satisfy the preferred ranges of dielectric constant and dielectric tangent of the present invention, so other evaluations were not performed.

[0098] <Peel strength from roughened surface of copper foil> The copper foil used was manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP, thickness 12 μm). The composition of Example 1 was press molded at 120 ° C, 5 MPa, and 2 minutes to obtain a 0.3 mm thick uncured sheet, and the roughened surface of the copper foil was placed in contact with the sheet. Using a 0.3 mm thick mold, the sheet was heated and pressed at a pressure of 5 MPa, 120 ° C for 30 minutes, then 150 ° C for 30 minutes, and then 200 ° C for 120 minutes, to bond and cure the sheet and the copper foil. The peel strength with the copper foil was evaluated by peeling at 90 ° in accordance with Japanese Industrial Standards (JIS) C6481:1996. As a result, the peel strength was 2.3 N / mm. The peel strength with the copper foil of the composition of Example 4 was also measured in the same manner, and was 1.5 N / mm.

[0099] <Synthesis of ethylene-styrene-divinylbenzene copolymer oligomer> With reference to the manufacturing method described in JP-A-9-40709, a 10L autoclave equipped with a stirrer and a jacket for heating and cooling was used, and polymerization was carried out using dimethylmethylenebiscyclopentadienylzirconium dichloride as a catalyst, methylalumoxane (Toso Fine-Chem, MMAO-3A toluene solution) as a cocatalyst, cyclohexane as a solvent, and styrene, divinylbenzene, and ethylene as raw materials, while appropriately changing the monomer amount, ratio, polymerization pressure, and polymerization temperature. 1-Isopropanol was added to the obtained polymerization liquid, and then a large amount of methanol was added in the presence of a polymerization inhibitor to recover a copolymer oligomer. This copolymer oligomer O-1 was vacuum dried at 50°C for two days and nights.

[0100] <Olefin-aromatic vinyl compound-aromatic polyene copolymer> The amount of monomers, ratio, polymerization pressure, and polymerization temperature were appropriately changed with reference to the manufacturing methods described in JP 2009-161743 A and JP 2010-280771 A to obtain copolymer P-5. The total of the olefin monomer unit, the aromatic vinyl compound monomer unit, and the aromatic polyene monomer unit was set to 100% by mass. The composition, number average molecular weight, and glass transition temperature of the obtained O-1 and P-5 are shown in Table 3.

[0101] As the bismaleimide, BMI-1500 manufactured by Designer Molecules Inc. was used.

[0102] Silica was Denka fused silica, SFP-130MC (d50 = 0.6 μm, specific surface area 6.2 m 2 / g, true specific gravity 2.26g / cm 3 ) was used without pretreatment.

[0103] [Table 3]

[0104] Examples 9 and 10 In a container equipped with a heating / cooling jacket and stirring blade, the raw materials other than the curing agent were charged in the composition shown in Table 4, heated to 60°C, and stirred to obtain a varnish-like (viscous liquid) composition. The curing agent was then added and stirred to dissolve. Perhexine 25B was used as the curing agent. The obtained varnish-like composition was poured into a Teflon (registered trademark) mold on a Teflon (registered trademark) sheet, and the solvent was thoroughly removed using a blower dryer at about 60°C, and then under reduced pressure. The obtained sheet was sandwiched between mirror-finished metal plates together with the Teflon (registered trademark) sheet, and was pressed against each other under pressure, and was then heated at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes to be cured. After curing, the metal plate, Teflon (registered trademark) sheet, and mold were removed to obtain a cured sheet of the composition of the present invention.

[0105] Example 11 A silica filler (50% by volume of silica filler to 50% by volume of resin component) was added to the varnish-like composition obtained in the same manner as in Examples 9 and 10, and the mixture was further stirred. The resulting slurry-like varnish was further stirred with a Blitzer Mixer (manufactured by Thinky Corporation), poured into a Teflon (registered trademark) mold on a Teflon (registered trademark) sheet, and the solvent was thoroughly removed using a blower dryer at about 60°C, and then under reduced pressure. The resulting sheet was sandwiched between mirror-finished metal plates together with the Teflon (registered trademark) sheet, and was pressed against each other under pressure, and then heated at 120°C for 30 minutes, 150°C for 30 minutes, and then 200°C for 120 minutes to be cured. After curing, the metal plate, Teflon (registered trademark) sheet, and mold were removed to obtain a cured sheet of the composition of the present invention.

[0106] [Table 4]

[0107] The cured products obtained in Examples 9 and 10, and the cured product containing the filler obtained in Example 11 all satisfy the conditions for the cured product of the present invention.

[0108] Examples 12 and 13 <Evaluation as an adhesive between copper foil and LCP (liquid crystal polymer) sheet> The varnish obtained in Examples 9 and 10 was used to evaluate the adhesion between the copper foil and the LCP sheet as follows. The copper foil was the above-mentioned copper foil, and the LCP sheet was the LCP resin (product number A-5000, melting point 280 ° C.) manufactured by Ueno Pharmaceutical Co., Ltd., obtained by the method described in International Publication WO2020 / 153391. A 100 μm thick sheet was used. The varnish was applied onto the LCP sheet, and the solvent was first removed by air drying at 60 ° C., and then the solvent was carefully and thoroughly removed so as not to cause foaming under normal pressure to vacuum at 60 ° C. The thickness of the varnish layer after solvent removal was about 30 μm. The roughened surface of the copper foil was attached to the varnish side of the sheet from which the solvent had been removed, and the sheet was heat-treated at 120 ° C. for 30 minutes, 150 ° C. for 30 minutes, and then 180 ° C. for 120 minutes while applying a pressure of 5 MPa with a vacuum press machine to harden the sheet. The sheet was cut to a width of 10 mm and a length of 100 mm, and the peel strength between the LCP sheet and the copper foil was evaluated by 90° peeling in accordance with Japanese Industrial Standards (JIS) C6481:1996. When the varnish obtained in Example 9 was used, the peel strength was 1.4 N / mm. When the varnish obtained in Example 10 was used, the peel strength was 1.3 N / mm. When the peeled surface was observed, peeling occurred at the interface between the varnish-derived cured body and the LCP sheet, so it was concluded that the peel strengths between the LCP sheet and the varnish-derived cured body were 1.4 N / mm and 1.3 N / mm, respectively. It was also concluded that the peel strengths between the copper foil and the varnish-derived cured body in the same test piece were higher than the above values.

[0109] Comparative Example 5 Using only the copper foil and the LCP sheet, heat and pressure bonding was carried out using a press under the same conditions as in the Example, but the two did not substantially adhere to each other.

[0110] <Example of the second aspect> Copolymers P-1a to P-4a according to the second embodiment were prepared using the following raw materials and with the compositions shown in Table 5 by the above-mentioned production method.

[0111] The divinylbenzene used was divinylbenzene (mixture of meta and para, divinylbenzene purity 81%) manufactured by Nippon Steel & Sumikin Chemical Co., Ltd. The BVPE (1,2-bis(vinylphenyl)ethane) was synthesized by the synthesis method described in JP-A-2003-212941 and used. It is a mixture of mm, mp, and pp bodies. The 1,2-PBd used was B-3000 manufactured by Nippon Soda Co., Ltd. The bifunctional polyphenylene ether oligomer (OPE-2St, number average molecular weight 1200) was obtained by diluting a toluene solution product manufactured by Mitsubishi Gas Chemical Co., Ltd. with toluene, adding a large amount of methanol, performing methanol precipitation, air drying, and drying under reduced pressure to obtain a powdered polyphenylene ether oligomer. The SEBS used was H-1041 manufactured by Asahi Kasei Chemicals Corporation. The curing agent used was dicumyl peroxide (Percumyl D) manufactured by NOF Corporation.

[0112] [Table 5]

[0113] The compositions and other details of the Examples and Comparative Examples are shown in Table 6.

[0114] [Table 6]

[0115] Example 1a Using a Brabender Plasticorder (Brabender PL2000), copolymer P-1a (ethylene-styrene-divinylbenzene copolymer) and monomers that had been kneaded in advance were added and kneaded for 5 minutes at 100°C and a rotation speed of 50 rpm, and then 1 part by mass of a curing agent (dicumyl peroxide, NOF Corp.) was added per 100 parts by mass of the copolymer and monomers combined, and kneaded under conditions of 100°C, a rotation speed of 50 rpm, and 5 minutes to prepare a composition. The resulting composition was sandwiched between a mold and two Teflon (registered trademark) sheets, closely attached and sealed, and pressed by a hot press method (120°C, time 5 minutes, pressure 5 MPa) to obtain sheets (uncured sheets) of various thicknesses (thickness 1.0 mm, 0.5 mm, etc.). The obtained sheet together with the Teflon (registered trademark) sheet was sandwiched between glass plates under a load to adhere them tightly, and cured by heat treatment for 30 minutes at 120° C., 30 minutes at 150° C., and then 120 minutes at 180° C. After curing, the glass plates, Teflon (registered trademark) sheet, and mold were removed to obtain a film-like cured product of the composition of the present invention.

[0116] Examples 2a to 4a, Comparative Examples 1a to 2a Compositions were prepared according to the same procedure as in Example 1a, with the formulations in Table 6 (the formulations in the table indicate parts by mass). Press molding and curing were carried out in the same manner as in Example 1a. The properties of the compositions before curing in Examples 1a to 4a (at room temperature) were all soft resin-like or semi-hard resin-like sheets, which were easy to handle as sheets, and even after being peeled off from the Teflon (registered trademark) sheet after pressing, the self-adhesiveness of the sheet itself was low, and it could be handled as a single sheet. Examples that satisfied the preferred conditions of the present invention were easy to mold as a thermoplastic resin in an uncured state.

[0117] On the other hand, in Comparative Examples 1a and 2a, a glass container equipped with a stirrer and a hot water jacket was used, and the raw materials were kneaded by stirring at about 60°C in advance, a curing agent was added, and kneading was further performed under these conditions for 10 minutes. Press molding and curing treatment were performed in the same manner as in Example 1a. The properties (room temperature) of the compositions obtained in both Comparative Examples 1a and 2a before curing were semi-solid viscous resin-like. When peeled off from the release sheet (Teflon (registered trademark) sheet), they showed blocking properties, were highly self-adhesive, and were difficult to handle as a single sheet, and could only be handled in a state sandwiched between release sheets.

[0118] The cured compositions obtained in Examples 1a to 4a were capable of measuring the elastic modulus even at 300°C in a viscoelastic spectrum measurement without melting or breaking, and had a storage modulus of 5×10 5 The crosslink density calculated from the storage modulus at 300°C (573K) was 3×10 -5 mol / cm 3 The values ​​were higher than those shown in Table 1, indicating that crosslinking had progressed sufficiently. All of the films exhibited a tensile modulus of less than 3 GPa and 3 MPa or more. Furthermore, the tensile strength at break was 5 MPa or more and less than 50 MPa, and the tensile elongation at break was 50% or more and less than 250%. The dielectric constant and dielectric tangent also satisfied the ranges of the present invention. The cured films obtained in Examples 1a to 4a all had a water absorption rate of less than 0.1% by mass, and a volume resistivity of 1×10 15 On the other hand, the cured sheets obtained in Comparative Examples 1a and 2a had too low tensile modulus at room temperature, and did not satisfy the conditions of the present invention in terms of storage modulus at 300°C and crosslink density.

[0119] <Peel strength from roughened surface of copper foil> The copper foil used was manufactured by Mitsui Mining & Smelting Co., Ltd. (VSP series, TQ-M7-VSP, thickness 12 μm). The composition of Example 1a was press-molded at 120 ° C, 5 MPa, and 2 minutes to obtain a 0.3 mm thick uncured sheet, and the roughened surface of the copper foil was placed in contact with the uncured sheet. Using a 0.3 mm thick mold, the sheet and the copper foil were bonded and cured by heating and pressing at a pressure of 5 MPa, 120 ° C for 30 minutes, then 150 ° C for 30 minutes, and then 180 ° C for 120 minutes using a heating press machine. The peel strength between the copper foil and the sheet was evaluated by peeling at 90 ° in accordance with Japanese Industrial Standards (JIS) C6481:1996. As a result, the peel strength was 1.7 N / mm.

[0120] From the above results, the cured product obtained by curing the composition of the present invention has excellent low dielectric properties and electrical insulation properties, exhibits a specific range of elastic modulus, heat resistance, and water resistance, and has a practically sufficient strength (elastic modulus) at room temperature and high temperature ranges. In addition, the peel strength with copper foil was also practically sufficient. Furthermore, it can exhibit high peel strength with LCP (liquid crystal polymer) sheets under relatively mild conditions. The present curable composition can exhibit a solid state that can be molded into a film, and exhibits thermoplasticity that can be melted by heating under the curing conditions or less, molded into various shapes, and cured. Therefore, it is easy to mold into various shapes including sheets, and can be subsequently cured by heating. The cured product can be suitably used as an electrical insulating material, particularly for high frequency applications. The present cured product can be suitably used as a thin-film electrical insulating material and an electrical insulating material for high frequency applications. In particular, the present invention can be used in a composition that contains a small amount of monomer (monomer) components, and can be substantially free of monomer components. The composition of the present invention can be used in an uncured state as a coverlay film, a solder resist film, a build-up film, a bonding sheet, a coverlay sheet, a bump sheet for flip chip bonders, an interlayer insulating agent, and an interlayer adhesive. The present invention can be used as a printed circuit board, a flexible printed circuit board, a CCL (copper clad laminate) substrate, an FCCL (flexible copper clad laminate) substrate, and further as an insulating layer for a substrate.

Claims

1. The curable composition satisfies the following conditions (1) to (4): an olefin-aromatic vinyl compound-aromatic polyene copolymer; and a curable composition comprising more than 0 parts by mass and not more than 10 parts by mass of a monomer per 100 parts by mass of the copolymer, wherein the monomer is one or more selected from the group consisting of an aromatic vinyl compound monomer, an aromatic polyene monomer, and a polar monomer having a difunctional or higher polyfunctional group. (1) The number average molecular weight of the copolymer is 5,000 or more and 100,000 or less. (2) The aromatic vinyl compound monomer in the copolymer is an aromatic vinyl compound having 8 to 20 carbon atoms, and the content of the aromatic vinyl compound monomer unit is 0% by mass or more and 70% by mass or less. (3) The aromatic polyene is one or more selected from polyenes having 5 to 20 carbon atoms and having a plurality of vinyl groups and / or vinylene groups in the molecule, and the content of the vinyl groups and / or vinylene groups derived from the aromatic polyene units is 1.5 or more and less than 20 per number average molecular weight. (4) The olefin is one or more olefins selected from olefins having from 2 to 20 carbon atoms, and the total of the olefin monomer units, aromatic vinyl compound monomer units and aromatic polyene monomer units is 100 mass %.

2. The curable composition according to claim 1 , wherein the monomer is a polar monomer having a difunctional or higher polyfunctional group.

3. A cured product obtained by curing the curable composition according to claim 1 or 2, which has a storage modulus at 300°C of 5 x 10 5 The electrical insulating material has a dielectric constant of 2.0 to 2.5 Pa at 23° C. and 10 GHz, and a dielectric loss tangent of 0.003 to 0.0005.

4. A laminate comprising a layer comprising the curable composition according to any one of claims 1 to 3 and a copper foil.

5. A laminate comprising a layer comprising the curable composition according to any one of claims 1 to 3 and an LCP layer.

6. A laminate comprising a layer comprising the curable composition according to any one of claims 1 to 3, a copper foil and an LCP layer.

7. A cured product obtained by curing the laminate according to any one of claims 4 to 6.

Citation Information

Patent Citations

  • Method to form droppout preventive angle for speeddchange gear fitted to automobiles

    JP1977031272A

  • Thermosetting resin composition having low dielectric constant

    JP1994192392A

  • Heat-resistant low-permitivity polymer material, and film, substrate board, electronic part and heat-resistant resin molding prepared from the same

    JP1999060645A

  • Electronic part for high frequency using low dielectric loss tangent insulating material

    JP2004087639A

  • Post curing resin composition and high frequency electrical insulating material using the same

    JP2009161743A